VD_FINDINFO Jug / 2016 / 356 vom 29. April 2016 - VD Tribunal cantonal (2016)
PORNOGRAPHIE, PEINE PRIVATIVE DE LIBERTÉ, DÉTENTION ILLICITE, PSYCHOTHÉRAPIE | 19 al. 2 CP, 40 CP, 47 CP, 49 al. 1 CP, 49 al. 2 CP, 50 CP, 51 CP, 56 CP, 57 al. 1 CP, 59 al. 3 CP, 69 CP, 89 al. 1 CP, 89 al. 6 CP